Recent progress in 2D metal-organic framework photocatalysts: synthesis, photocatalytic mechanism and applications. (28th May 2021) - Pan, Yangdan; Abazari, Reza; Yao, Juming; Gao, Junkuo
Abstract: 2D metal-organic framework (2D MOF) nanosheets and their derived nanocomposites have been widely studied in recent years due to their ultrathin atomic-level thickness, large surface area and adjustable structure. This review is thus aimed at summarizing the recent studies on synthesis methods and the photocatalytic mechanism of 2D MOF nanosheets. The synthesis methods can be concretely divided into top-down and bottom-up methods, including physical and chemical exfoliation, interfacial synthesis, three-layer synthesis and surfactant-assisted synthesis. The photocatalytic mechanisms can also be categorized into three classes: photo-absorption, photo-generated carrier separation and transport, and surface redox reaction. Moreover, the applications of 2D MOF nanosheets in the field of photocatalysis, including photocatalytic hydrogen evolution, photocatalytic CO2 reduction, photocatalytic degradation and organic chemical photosynthesis, were also briefly discussed. Finally, some challenges and expectations with regard to 2D MOF nanosheets in photocatalysis will be addressed.